2021
DOI: 10.1021/acsnano.0c10788
|View full text |Cite
|
Sign up to set email alerts
|

Anodized Nickel Foam for Oxygen Evolution Reaction in Fe-Free and Unpurified Alkaline Electrolytes at High Current Densities

Abstract: To achieve practically high electrocatalytic performance for the oxygen evolution reaction (OER), the active surface area should be maximized without severely compromising electron and mass transport throughout the catalyst electrode. Though the importance of electron and mass transport has been studied using low surface area catalysts under low current densities (∼tens of mA/cm2), the transport properties of large surface area catalysts under high operating current densities (∼500 mA/cm2) for practical OER ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 58 publications
(133 reference statements)
7
92
0
Order By: Relevance
“…In order to understand the ORR reaction kinetics in depth, the corresponding Tafel slopes are plotted and displayed in Figure c. In general, a lower Tafel slope at a low overpotential region implies efficient kinetics in the catalytic process. , Interestingly, the Co@IC/MoC@PC sample also possesses the smallest Tafel slope of 78 mV/dec, thus suggesting its excellent kinetics. The charge-transfer resistance could be measured by the electrochemical impedance spectroscopy (EIS).…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the ORR reaction kinetics in depth, the corresponding Tafel slopes are plotted and displayed in Figure c. In general, a lower Tafel slope at a low overpotential region implies efficient kinetics in the catalytic process. , Interestingly, the Co@IC/MoC@PC sample also possesses the smallest Tafel slope of 78 mV/dec, thus suggesting its excellent kinetics. The charge-transfer resistance could be measured by the electrochemical impedance spectroscopy (EIS).…”
Section: Resultsmentioning
confidence: 99%
“…Smith’s group, using the density functional theory and near-infrared spectroscopy, indicated that the additive cations asymmetrically affect the voltage-induced expansion and contraction of the nickel hydroxide lattice . The peak at 1.39 V could be related to such Ni sites. …”
Section: Resultsmentioning
confidence: 99%
“…178 Alternatively, one can settle using Ni mesh as an anode that can be activated by anodization or used as a Ni source for the formation of OER active NiFeOOH. 169,179,180 Although pure Ni mesh is not highly active, its stability under operation conditions is remarkable. For example, the anode performance loss is less than 0.5% per year for commercial Ni mesh anodes with an expected lifetime of more than 5 years.…”
Section: Key Parameters In Evaluating Catalyst Degradationmentioning
confidence: 99%
“…181 Controlling the reaction rate between oxidation and dissolution is needed to nanostructure the metal foams. 169,181 Fluoride-free approaches include cathodic deposition of nanostructured Ni deposit from the electrolyte containing Ni 2+ salts followed by anodic oxidation. 182 Recently, Wan et al 168 reported anodic oxidation of Ni foam in 1−10 M KOH at 1−3 A cm −2 for 3 h, where metal oxidation and oxygen evolution occur simultaneously to give a nanostructured electrode.…”
Section: Key Parameters In Evaluating Catalyst Degradationmentioning
confidence: 99%